Accuracy of Bedside Lung Ultrasound in Emergency (BLUE) Protocol to Diagnose the Cause of Acute Respiratory Distress Syndrome (ARDS): A Meta-Analysis - Oke Dimas Asmara; Ceva Wicaksono Pitoyo; Vally Wulani; Kuntjoro Harimurti; Abrianty P Araminta (Interna Publishing, 2022)
Background: There is a stigma that ultrasound cannot be used to see abnormalities in the air-filled organs makes ultrasound rarely used to identify lung abnormalities. This study purpose comparing diagnostic accuracy of BLUE protocol with gold standard for each diagnosis causing acute respiratory failure. Methods: Systematic search was done in 6 databases (Pubmed/MEDLINE, Embase, Cochrane Central, Scopus, Ebscohost/CINAHL dan Proquest) and multiple grey-literature sources for cross-sectional studies. We manually extracted the data from eligible studies and calculated pooled sensitivity, pooled specificity, likelihood ratio (LR) and diagnostic odds ratio (DOR). We follow PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) guideline throughout these processes. Results: Four studies has been picked from total 509 studies involved. The results yield parameters indicating BLUE protocol as a reliable modality to diagnose pneumonia with pooled sensitivity 84% (95% CI, 76-89%),  pooled specificity 98%  (95% CI, 93-99%), LR+ 42 (95% CI, 12-147), LR- 0.12 (95% CI, 0.07-0.2) and DOR 252 (95% CI, 81-788), respectively. It also considerably applicable to diagnose pulmonary oedema with pooled sensitivity 89% (95% CI, 81-93%), pooled specificity 94% (95% CI, 89-96%), LR+ 14 (95% CI, 8-25), LR- 0.165 (95% CI, 0.11-0.24), and DOR 116 (95% CI, 42-320), respectively. Conclusion: BLUE protocol has good diagnostic accuracy to diagnose pneumonia and pulmonary oedema. We recommend implementing BLUE protocol as a tool in evaluating cause of ARF.